(untitled) (Bangladesh Journal of Botany, 2012)
Screening of 25 potato germplasms against Rhizoctonia solani BTB115 in artificially infested field condition were carried out. No germplasm was found resistant to R. solani. Only six germplasms appeared to be moderately resistant. Cardinal, Diamant and Heera were found as highly susceptible varieties. True potato seed BARI TPS1 was tested against two virulent isolates of R. solani DK64 and BTB115. Only 21% and 29% resistant seedlings against the DK64 and BTB115 isolates, respectively were obtained compared to 85% seedlings in control. Keywords: Germplasm; Potato; TPS; Rhizoctonia solani DOI: http://dx.doi.org/10.3329/bjb.v40i2.9777 Bangladesh J. Bot. 40(2): 193-196, 2011 (December)